Trophic resources and mercury exposure of two silvertip shark populations in the Northeast Pacific Ocean. (August 2020) - Le Croizier, Gaël; Lorrain, Anne; Schaal, Gauthier; Ketchum, James; Hoyos-Padilla, Mauricio; Besnard, Lucien; Munaron, Jean-Marie; Le Loc'h, François; Point, David
Abstract: Worldwide shark populations have experienced rapid declines over the last decades, mainly due to overfishing. Marine protected areas (MPAs) have thus become an indispensable tool for the protection of these marine predators. Two recently-created MPAs in the Northeast Pacific Ocean, the Revillagigedo National Park and Clipperton Atoll, are characterized by different trophic structures potentially influencing the trophic niche and contaminant exposure of resident sharks in these two sites. In this context, we used carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyzes as well as total mercury concentrations ([THg]) to assess the effect of foraging site on the trophic niche and Hg levels of juvenile silvertip (ST) sharks Carcharhinus albimarginatus . Analyzing fin clip samples from Revillagigedo and Clipperton, we found that shark δ 15 N varied spatially in relation to δ 15 N baselines, suggesting similar trophic position in both MPAs. Moreover, δ 13 C values indicated that ST sharks from Revillagigedo would feed on different food webs ( i.e. both benthic and pelagic) while individuals from Clipperton would only rely on benthic food webs. These differences between MPAs led to a weak overlap of isotopic niches between the two populations, highlighting the site residency of juvenile ST sharks. Within each population, [THg] was not correlated with trophic tracers (δ 15 N and δ 13 C) and was also similar between populations. This study revealed no influence of site or food web in [THg] and raises the question of the origin of Hg exposure for reef shark populations in the Northeast Pacific Ocean. Graphical abstract: Image 1 Highlights: Silvertip sharks fed on both pelagic and benthic food webs at Revillagigedo. The population from Clipperton relied only on benthic food webs. Hg levels do not seem to vary between sites or food webs. Weak niche overlap between populations reflected site residency of silvertip sharks.